In-plane compressive properties of assembled auxetic chiral honeycomb composed of slotted wave plate - Zhang, Yi; Ren, Xin; Jiang, Wei; Han, Dong; Yu Zhang, Xiang; Pan, Yang; Min Xie, Yi (Materials & design, 2022)
[Display omitted] •An assembled auxetic chiral honeycomb (AACH) is designed and manufactured by 3D printing.•The AACH could exhibit lower peak force and high stress plateau.•The external energy is mainly absorbed by the vertical wave plate.•The AACH provides a new idea for the industrial manufacturing of auxetics. Auxetic metamaterials tend to be fabricated using additive manufacturing and laser cutting due to their special porous microstructures. Although the auxetic metamaterials have many applications currently, the high cost and the low efficiency of available manufacturing are adverse to expend their application range. In this work, the auxetic chiral honeycomb is assembled crosswise using the slotted wave plate. Effects of wave radius, plate thickness, slot percentage, and base material on the Poisson’s ratio and mechanical performance are explored experimentally and numerically. The results show that assembled auxetic chiral honeycomb (AACH) exhibits lower peak force and high plateau stress than the conventional assembled one. With the increase of wave radius and plate thickness, the energy absorption (EA) and specific energy absorption (SEA) would increase. As for the different material combinations, when the base materials in vertical and horizontal wave plates adopt stainless steel and aluminum, respectively, the AACH would exhibit desirable EA, SEA, and auxetic behavior. These findings provide a new approach to the manufacture of auxetics at a low cost, which is beneficial for potential applications.